Urgensi Pendidikan Revolusi Mental Dalam Pembentukan Karakter Peserta Didik Pada Mata Pelajaran PAI Di SMA Plus Astha Hannas Subang - Ibad, Faizul; Nur Kabibuloh (Fakultas Keguruan dan Ilmu Pendidikan Universitas Nahdatul Ulama Indonesia, 2024)
This study aims to analyze the implementation of Mental Revolution Education in shaping students' character at SMA Plus Astha Hannas Subang, focusing on its concept, implementation, strengths, and weaknesses. A qualitative descriptive method was used in this research. The participants included the principal, vice principal, Islamic education teacher, and students. Data were collected through observations, interviews, and documentation. The results show that the concept is integrated into the hidden curriculum through training and mentoring programs that aim to instill national values in students. The implementation of Mental Revolution Education is carried out through internalizing its principles using strategies such as role modeling, training and habituation, teaching, giving advice, and enforcing discipline. The main strength of this program lies in producing outstanding graduates, while its main weakness is that the learning process requires considerable time and ongoing effort.